2017
DOI: 10.1021/acs.biomac.7b01469
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymer Nanoparticles for Photodynamic Therapy by Bioluminescence Resonance Energy Transfer

Abstract: Conventional photodynamic therapy is severely constrained by the limited light-penetration depth in tissue. Here, we show efficient photodynamic therapy (PDT) mediated by bioluminescence resonance energy transfer (BRET) that overcomes the light-penetration limitation. The photosensitizer Rose Bengal (RB) was loaded in biodegradable poly(lactic-co-glycolic acid) (PLGA) nanoparticles, which were then conjugated with firefly luciferase. Spectroscopic characterizations indicated that BRET effectively activated RB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 37 publications
0
42
0
1
Order By: Relevance
“…Furthermore, this BL-PDT can also suppress distant organ metastasis. Recently, Yang et al ( 2018 ) reported a new BL-PDT system based on the polymer nanoparticle which was assembled from poly(lactic acid) and poly(lactic- co -glycolic acid) and was loaded with Rose Bengal and luciferase. In vitro photodynamic studies showed that this BL-PDT treatment can lead to significant toxicity toward cancer cells.…”
Section: Bioluminescence-mediated Photodynamic Therapymentioning
confidence: 99%
“…Furthermore, this BL-PDT can also suppress distant organ metastasis. Recently, Yang et al ( 2018 ) reported a new BL-PDT system based on the polymer nanoparticle which was assembled from poly(lactic acid) and poly(lactic- co -glycolic acid) and was loaded with Rose Bengal and luciferase. In vitro photodynamic studies showed that this BL-PDT treatment can lead to significant toxicity toward cancer cells.…”
Section: Bioluminescence-mediated Photodynamic Therapymentioning
confidence: 99%
“…Finally, BRET-based photoinduction has potential for therapeutic use as well, as demonstrated by Yang et al [157]. The authors demonstrated efficient photodynamic therapy (PDT) using BRET-based localized excitation to inhibit tumor growth in a mouse model.…”
Section: In Vivo Bretmentioning
confidence: 99%
“…Excised tumors from the five groups visually show the successful tumor growth inhibition by PDT for the PLGA-RB with external light excitation and PLGA-RB with BRET (Figure 13D). PDT using BRET is an interesting way to impact tumor cells in deep tissues, where external light sources struggle to penetrate [157].…”
Section: In Vivo Bretmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the use of near-infrared light with longer wavelength (650–1000 nm) through upconversion, such as two-photon,4,5 upconverting nanoparticles,2 and triplet–triplet annihilation,9 is proposed to improve tissue penetration, but it only increases to millimetre depths. Self-luminescence, including chemiluminescence (CL),10–23 bioluminescence,24–27 and Cerenkov radiation,28 are now deemed to have more potential as tissue-penetration-depth-independent light and has been successfully applied in the highly sensitive bioimaging field 8. However, self-luminescence-driven photoisomerization in vivo remains extremely challenging because such a low-intensity light source insufficiently implements a good photoisomerization effect 8.…”
Section: Introductionmentioning
confidence: 99%